The intersection of syntax and poetry in the first Hebrew acrostic poem of Lamentations - Naudé, Jacobus A.; Miller-Naudé, Cynthia L. (Stellenbosch Papers in Linguistics Plus, 2023)
Acrostic poems in Biblical Hebrew are structured both by the successive letters of the Hebrew alphabet at the beginning of successive strophes as well as by the ordinary features of poetic style. In this essay we consider how these two aspects of poetic style interact with the poet’s syntactic choices in the first poem of the Book of Lamentations (1:1-11) in order to determine to what extent the poetic constraints have hampered or warped the syntactic structures employed in the poetic lines or half-lines.